Using MaxEnt to Predict the Potential Distribution of the Little Fire Ant (Wasmannia auropunctata) in China - Mengfei Mao; Siqi Chen; Zengyuan Ke; Zengqiang Qian; Yijuan Xu (Insects, 2022)
Invasive ants are some of the most destructive species in ecosystems and can have serious ecological and socioeconomic impacts. The little fire ant, Wasmannia auropunctata, is native to Central and South America and was listed as one of the 100 most threatening major invasive organisms in the world by the International Union for Conservation of Nature (IUCN). The presence of W. auropunctata was first reported on the Chinese mainland in January 2022, but its distribution in China is still unclear. In this study, MaxEnt was used to predict the potential distribution of W. auropunctata in China based on known distribution points and climatic variables. The prediction results showed that most of the area south of the Yangtze River is potentially suitable for W. auropunctata, and temperature is the main factor affecting its distribution. The contemporary total suitable living area of W. auropunctata is 1,954,300 km2, accounting for 20.36% of China’s total land area. Further attention should be given to the potential impact of W. auropunctata invasions, and effective measures should be taken to eliminate the introduced population in China.